The world according to Peter Drucker - Beatty, Jack (Broadway, 1998)
Peter Drucker is arguably the most influential architect of today's corporate society. Yet no concise overview of his life and work has ever appeared--until now. Creating a Drucker primer as much as a biography, Jack Beatty has distilled the essence of Drucker's beliefs and strategies into one engaging volume. Spanning Drucker's childhood in Vienna during the first world war, through his first American teaching jobs when raging factions debated the best form of government (if any), to his immersion in modern management theory using General Motors as a model, and finally, to the era of downsizing facing his Fortune 500 clients, The World According to Peter Drucker also captures our own corporate evolution in this century.